HUBUNGAN BERAT BADAN LAHIR DAN UMUR KEHAMILAN DENGAN FREKUENSI MENYUSUI PADA IBU MENYUSUI DI POSYANDU KELURAHAN SEI HARAPAN KECAMATAN SEKUPANG KOTA BATAM TAHUN 2017 - Susilawati, Endang; Ibrahim, Ibrahim (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
The breast milk production of newborn’s mother is influenced by various factors for instance the frequency of breastfeeding, infants birth weight, gestational age, and maternal nutritional status. Hence, this study aims to determine the correlation of newborns birth weight and gestational ages on frequency of the mothers in breastfeeding their babies. This study is designed as an analytic survey research with cross sectional approach. For the population, the researchers took 0 to 23 month infants’ mothers to be investigated, and further, 90 respondents were derived as the sample through simple random sampling technique which conducted in June 2017. As the research instrument, questionnaires were distributed to the respondents. The data gathered was analyzed by Chi Square statistical test. The results expose that most of the newborns, close to 81.1%, were born with normal body weight, on the other hand, 68.9% considered to meet the due-date of the gestational age, and 80.0% mothers experienced high breastfeeding frequency. It was noted the correlation of babies birth weight with p value = 0,005 and gestational age with p value = 0,003 to the mothers breastfeeding frequency. Therefore, it can be concluded that there is a significant correlation of the newborns birth weight and gestational age of the pregnancy on the mothers’ breastfeeding frequency, particularly in the service area of Sei Harapan Integrated Health Post (posyandu) of Sekupang, Batam in 2017.  Finally, it is hoped the respondents to dig out more information from various sources to enhance their knowledge and understanding on the factors that potentially affect the breastfeeding.